Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jtcvs.2015.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgical strategy on survival after repair of type A aortic dissection

Abstract: The operative strategy of group 1 (no cross-clamp, use of DHCA and antegrade perfusion) was associated with a highly significant improvement in survival, despite a lack of statistical difference in the incidence of persistent false aortic lumen between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 24 publications
(32 reference statements)
0
32
0
Order By: Relevance
“…2 The single approach in our recent report that strictly adhered to the points stressed by David and colleagues 1 in their landmark article written in 1999 (in an effort to reduce operative mortality) and highlighted in Figure 1 of his recent contribution 3 was found to be associated with the lowest long-term mortality when compared with the other surgical approaches. These principles included the avoidance of an aortic crossclamp, performance of an open distal anastomosis, and perfusion in the antegrade fashion via the graft after completion of the distal anastomosis.…”
mentioning
confidence: 79%
“…2 The single approach in our recent report that strictly adhered to the points stressed by David and colleagues 1 in their landmark article written in 1999 (in an effort to reduce operative mortality) and highlighted in Figure 1 of his recent contribution 3 was found to be associated with the lowest long-term mortality when compared with the other surgical approaches. These principles included the avoidance of an aortic crossclamp, performance of an open distal anastomosis, and perfusion in the antegrade fashion via the graft after completion of the distal anastomosis.…”
mentioning
confidence: 79%
“…Perfusion strategy is also an important aspect to repair of type A dissection, regardless of the extent of repair. In a publication from Washington University in St. Louis in 2015 examining 196 patients who underwent repair of type A dissection [16], we found that avoidance of cross-clamping, use of deep hypothermic circulatory arrest, and antegrade reperfusion after aortic replacement were associated with the best long-term survival. Although there was some selection bias in this report favoring a less-aggressive approach in patients whose long-term survival or functional state was in question, the absence of any one of these techniques was associated with a decrement in survival.…”
Section: Distal Extent Of Surgery In Type a Dissectionmentioning
confidence: 95%
“…Similarly, our group maintains an awareness that cross-clamp application can potentially increase the incidence of malperfusion, particularly when retrograde femoral perfusion is used. As this publication demonstrates, it is not only the extent of replacement of the aorta proximally and distally that is important but also the conduct of the operation and management of perfusion that contribute to long-term outcomes in type A dissection repair [16].…”
Section: Distal Extent Of Surgery In Type a Dissectionmentioning
confidence: 99%
“…The safety of femoral cannulation in general has been questioned, though, given concerns about pressurization of the false lumen and malperfusion, which could be compounded when the distal ascending aorta is cross-clamped (104,110,134). Evaluation of the risk associated with cross-clamping the aorta during the cooling phase and prior to PHCA have provided divergent results: some studies have reported increased risk (110,121,135), and others have failed to show excess morbidity or mortality (130,136).…”
Section: The Arch Cerebral Protection and Cannulation Strategymentioning
confidence: 99%